2014
DOI: 10.1080/15374416.2014.963858
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Parental ADHD in Sustaining the Effects of a Family-School Intervention for ADHD

Abstract: Objective This study investigated the extent to which parental Attention-Deficit/Hyperactivity Disorder (ADHD) symptoms impact child and parent outcomes following a multimodal family-school intervention, the Family School Success (FSS) program, when compared to an active-control condition (CARE). Method Participants were 139 children with ADHD (67% male; 91% non-Hispanic; 77% Caucasian; grades 2–6) and their primary caretaker (91% female; aged 26–59) who participated in a randomized clinical trial evaluating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 52 publications
(78 reference statements)
0
22
0
Order By: Relevance
“…These studies vary widely in methodology (see Table 1 for methodological details for each of these studies), but have (with a few exceptions) found that parent ADHD (or elevated ADHD symptoms) are associated with reduced improvement in child ADHD and externalizing symptoms following behavioral treatment. These findings extend to domains of child impairment, such that parent ADHD also predicts less improvement in social relationships and academic functioning following behavioral interventions that target these domains (Dawson, Wymbs, Marshall, Mautone, & Power, 2014; Griggs & Mikami, 2011; Jensen et al, 2007; see Table 1). …”
Section: Parent Adhd and Child Behavior Therapy: Overview And Review mentioning
confidence: 74%
See 3 more Smart Citations
“…These studies vary widely in methodology (see Table 1 for methodological details for each of these studies), but have (with a few exceptions) found that parent ADHD (or elevated ADHD symptoms) are associated with reduced improvement in child ADHD and externalizing symptoms following behavioral treatment. These findings extend to domains of child impairment, such that parent ADHD also predicts less improvement in social relationships and academic functioning following behavioral interventions that target these domains (Dawson, Wymbs, Marshall, Mautone, & Power, 2014; Griggs & Mikami, 2011; Jensen et al, 2007; see Table 1). …”
Section: Parent Adhd and Child Behavior Therapy: Overview And Review mentioning
confidence: 74%
“…The mean number of parent ADHD symptoms in the study by Chronis-Tuscano et al (2011) met this clinical criteria (see Table 1). Other studies that categorically examined parent ADHD demonstrated parents in the “high ADHD symptoms” group also met this DSM-5 symptom threshold (e.g., Dawson et al, 2014; Griggs & Mikami, 2011). In sum, higher, clinical levels of parent ADHD symptoms seem to be associated with more negative child behavioral treatment outcomes.…”
Section: Parent Adhd and Child Behavior Therapy: Overview And Review mentioning
confidence: 98%
See 2 more Smart Citations
“…Also, research has shown ADHD's effects on family functioning to be twofold when a child in the family presents the disorder as well (Dawson, Wymbs, Marshall, Mautone, & Power, 2014). In addition, ADHD in parents has been reported to exacerbate their children's ADHD symptoms (ChronisTuscano & Stein, 2012).…”
Section: Introductionmentioning
confidence: 98%